2003
DOI: 10.1590/s0100-84042003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrospermopsis raciborskii (Woloszynska) Seenayya & Subba Raju(Cyanobacteria): variação semanal e relações com fatores ambientais em um reservatório eutrófico, São Paulo, SP, Brasil

Abstract: -(Cylindrospermopsis raciborskii (Woloszynska) Seenayya & Subba Raju (Cyanobacteria): weekly variation and relation with environmental factors in an eutrophic lake, São Paulo, SP, Brazil). Blooms of Cylindrospermopsis raciborskii have become more and more frequent in Brazilian reservoirs because of its high competitiveness in tropical eutrophic systems. This species is able to produce very aggressive toxins which cause problems to public health and environmental hazards. Our objective was to follow up variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
3
25
0
10
Order By: Relevance
“…These results seem to apply to other eutrophized reservoirs in Brazilian tropical regions and are consistent with those from several other authors: Beyruth (1996), Bouvy et al (1999), Matsuzaki (2004), Sant'Anna et al (1989,1997), Silva (1999) and Tucci & Sant'Anna (2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results seem to apply to other eutrophized reservoirs in Brazilian tropical regions and are consistent with those from several other authors: Beyruth (1996), Bouvy et al (1999), Matsuzaki (2004), Sant'Anna et al (1989,1997), Silva (1999) and Tucci & Sant'Anna (2003).…”
Section: Discussionsupporting
confidence: 92%
“…Komárková et al (1999) observed, while studying a coastal lagoon in the south of Brazil, that C. raciborskii may present great morphologic variety (straight, curved or spiral shapes) and that the species was the dominant one during periods of high temperature, low nitrogen concentration and high phosphorus concentration. Tucci & Sant'Anna (2003) studied the weekly variation of C. raciborskii in an eutrophic reservoir in São Paulo, in Brazil, and correlated the high density of that organism to high temperature and pH, high concentration of chlorophyll a, low water transparency, low concentrations of free carbonic gas and ammonium.…”
mentioning
confidence: 99%
“…When a Microcystis bloom occurs, their mucilaginous colonies provide a high degree of shading to the other phytoplanktonic species, thus disfavouring their growth. Consequently, diversity and richness decrease significantly [54]. Other factors that allow Microcystis dominance in many aquatic ecosystems are high nutrient loading; rising temperatures, because cyanobacteria generally grow better at higher temperatures than do other phytoplankton species; enhanced stratification, reducing water vertical mixing; physiological and biochemical adaptations to growth in a saline environment, and the presence of intracellular gas vesicles, which make the cells buoyant, shading underlying non-buoyant phytoplankton and suppressing their opponents through competition for light [55].…”
Section: Discussionmentioning
confidence: 99%
“…Group S N seemed to be favored by particular hydrological conditions in the lake during the warm-rainy period, such as high temperature and thermal stability of the water column (Branco and Senna, 1994;Tucci and Sant'Anna, 2003;Silva, 2004). Its distribution did not seem to be influenced by grazing, probably because of the ample availability of algae of appropriate sizes for herbivores.…”
Section: Discussionmentioning
confidence: 99%